A self-template strategy to prepare hollow NiMoS4 nanospheres supported on Ni foam as advanced supercapacitor electrodes. (1st April 2020) - Liu, Zhaohui; Pan, Chenhao; Li, Wen; Wei, Shuang; Zhang, Mutian; Chen, Shougang
Abstract: Pseudocapacitor has recently emerged as an important electrical energy storage technology that plays a critical role in portable electronic device, hybrid electric vehicle, backup energy system, and so on. In spite of the great advances, preparing ultra-stable pseudocapacitor with excellent electrochemical performance is still very challenging. Herein, we developed a simple but novel self-template method to synthesize hierarchical hollow NiMoS4 nanospheres with ultrathin shell thickness. During the preparation, nickel-molybdenum oxides coated SiO2 precursors were firstly synthesized. After a sulfidation process with Na2 S under hydrothermal condition, the precursors were transformed into hierarchical hollow NiMoS4 nanospheres. Simultaneously, the interior SiO2 was well etched by tuning the initial Ni/S molar ratio. In addition, hollow NiMoS4 nanospheres with different shell thickness were also prepared. Remarkably, the obtained NiMoS4 nanospheres show a very high electrochemical activity due to their fascinating structural and compositional features. The electrode prepared from the NiMoS4 nanospheres delivers a high specific capacity of 1094 C g −1 current density of 1 A g −1 with enhanced cycling stability of 97.95% capacitance retention after 10, 000 cycles, making them to be potential electrode materials for SCs and other related energy storage devices.